2016
DOI: 10.18632/oncotarget.12023
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CRNDE promotes gallbladder carcinoma carcinogenesis and as a scaffold of DMBT1 and C-IAP1 complexes to activating PI3K-AKT pathway

Abstract: Deleted in malignant brain tumors 1 (DMBT1) is deleted during cancer progression and as a potential tumor-suppressor gene in various types of cancer. However, its role in Gallbladder cancer remains poorly understood. DMBT1 has low-expression and deletion of copy number were detected in normal tissues and GBC cancer tissues by qRT-PCR. Knockdown of DMBT1 increased migration and invasion and overexpressed DMBT1 impaired migration and invasion in GBC cells. We also evaluated the molecular mechanism of DMBT1 by RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 29 publications
0
48
0
Order By: Relevance
“…It has been reported that lncRNA CRNDE is upregulated in several kinds of cancers. [14][15][16] In this research work, we initially detected the by coordinating and amplifying many signals in tumour cells. 35 Wang et al 36 showed that IRS1 expression was significantly boosted in both breast cancer cell lines and tissues, and overexpression of IRS1 could reverse miR-195-mediated repression of tumour cell proliferation; moreover, miR-195 inhibited tumour angiogenesis via IRS1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that lncRNA CRNDE is upregulated in several kinds of cancers. [14][15][16] In this research work, we initially detected the by coordinating and amplifying many signals in tumour cells. 35 Wang et al 36 showed that IRS1 expression was significantly boosted in both breast cancer cell lines and tissues, and overexpression of IRS1 could reverse miR-195-mediated repression of tumour cell proliferation; moreover, miR-195 inhibited tumour angiogenesis via IRS1.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we found that DMBT1 overexpression can remarkably curb the invasion and metastasis of CSCC cells. Coincidentally, Shen et al reported that overexpressed DMBT1 can modulate the PI3K‐AKT pathway, and thereby inhibiting the migration and invasion of GBC cells. In recent years, many studies have revealed that PI3K‐AKT signaling pathway is involved in the formation of EMT, which is the biological process that epithelial cells transform into interstitial phenotype cells through specific procedures .…”
Section: Discussionmentioning
confidence: 99%
“…Deleted in malignant brain tumor 1 (DMBT1), located on chromosome 10q25.3‐26.1, was initially found by Mollenhauer et al to be rearranged and/or deleted in two common malignant tumors (medulloblastoma and glioblastoma). Actually, many researchers have observed the deletion or reduction of DMBT1 expression in a variety of solid tumors, including gallbladder carcinoma, lung cancer, gastrointestinal cancers (esophageal, gastric, and colon cancers), breast cancer, and prostate cancer . As for cervical cancer, it has been well‐established that high‐risk human papillomavirus (HPV) infection is considered as the major cause of cervical cancer, which was detected in almost 99% of cervical cancer samples .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRNDE was upregulated in glioma stem cells (GSCs) and in human glioma tissues, and the overexpression of CRNDE was found to promote cellular proliferation, migration, and invasion and to inhibit apoptosis in GSCs [23]. CRNDE promoted gall bladder carcinoma carcinogenesis and served as a scaffold of DMBT1 and C-IAP1 complexes to activate the PI3K-AKT pathway [24]. Esposti found that CRNDE was upregulated in hepatocellular carcinoma using RNA sequencing [25].…”
Section: Discussionmentioning
confidence: 99%